PKM TRAINING AND EDUCATION FOR THE COMMUNITY "CONSTRUCTION SAFETY" IN PADANG - Melda Fajra; Maha Putri; Julita Andrini; Helny Lalan; Edo Adi Saputra; Afra Eliza Eprizon; Hari Rantoso (Journal of Community Service, 2024)
Construction safety is a crucial aspect in ensuring the continuity and quality of development projects. In Padang, there is still a gap in knowledge and awareness regarding work safety in the construction sector, especially among informal workers and the surrounding community. The Community Service Program (PKM) with the title "Training and Education for the 'Construction Safety' Community in Padang" aims to provide practical knowledge and skills regarding construction safety. This program involves several stages, including identification of training needs, preparation of materials, implementation of training, and monitoring and evaluation. The results of the implementation show a significant increase in awareness and application of work safety standards among participants, which is expected to reduce the number of work accidents and increase the efficiency and quality of construction projects in Padang